2005
DOI: 10.1128/mcb.25.16.7137-7143.2005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Watson-Crick Hydrogen Bonding Requirement in DNA Synthesis by Human DNA Polymerase κ

Abstract: The efficiency and fidelity of nucleotide incorporation by high-fidelity replicative DNA polymerases (Pols) are governed by the geometric constraints imposed upon the nascent base pair by the active site. Consequently, these polymerases can efficiently and accurately replicate through the template bases which are isosteric to natural DNA bases but which lack the ability to engage in Watson-Crick (W-C) hydrogen bonding. DNA synthesis by Pol, a low-fidelity polymerase able to replicate through DNA lesions, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
63
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 49 publications
5
63
1
Order By: Relevance
“…Moreover, there is a significant asymmetry in the efficiency of the extension reaction, an ϳ30-fold reduction for insertion of dATP opposite template DFT and ϳ900-fold reduction for insertion of d(DFT)TP opposite template A (relative to the corresponding processes with T and dTTP, respectively (5)). The latter loss is comparable with the effects on insertion reactions involving the DFT analog seen with Y-class polymerases (5,(7)(8)(9). Together, these observations appear inconsistent with the conclusion that A-and Y-class polymerases use different mechanisms of replication and that the former may rely chiefly on shape for efficient and correct nucleotide insertion (1,2).…”
contrasting
confidence: 44%
See 1 more Smart Citation
“…Moreover, there is a significant asymmetry in the efficiency of the extension reaction, an ϳ30-fold reduction for insertion of dATP opposite template DFT and ϳ900-fold reduction for insertion of d(DFT)TP opposite template A (relative to the corresponding processes with T and dTTP, respectively (5)). The latter loss is comparable with the effects on insertion reactions involving the DFT analog seen with Y-class polymerases (5,(7)(8)(9). Together, these observations appear inconsistent with the conclusion that A-and Y-class polymerases use different mechanisms of replication and that the former may rely chiefly on shape for efficient and correct nucleotide insertion (1,2).…”
contrasting
confidence: 44%
“…Conversely, their more open active sites may render Y-class polymerases (6 -10) less sensitive to changes in base pair dimensions but more dependent on formation of hydrogen bonds between nucleotide pairs at the replicative position (6 -9). A-class DNA polymerases whose activities were assessed using apolar T analogs to date include Escherichia coli pol I (3)(4)(5) and the polymerase from phage T7 (6), and the tested Y-class DNA polymerases consisting of yeast pol (7), human pol (8), and the Dbh (DinB homolog (5)) and Dpo4 (9) polymerases from Sulfolobus acidocaldarius and Sulfolobus solfataricus, respectively.…”
mentioning
confidence: 99%
“…A crystal structure of the HIV-1 RT-DNA-PMPA-DP ternary complex revealed that PMPA-DP forms a noncanonical Watson-Crick base pair (51). Thus, this suboptimal base-pairing scheme for PMPA-DP and dT may contribute to the lower catalytic efficiency for the human enzymes, since hydrogen bonding has been shown to be important for incorporation catalyzed by Pol ␥ (27), Pol (7), Saccharomyces cerevisiae Pol (54), Pol (56), and Rev1 (6). Overall, PMPA-DP appears to be a superior drug analog because it requires only two phosphorylation events to become activated, it is a better substrate for HIV-1 RT than the seven human enzymes examined thus far (Table 3) (23,50), and it has a favorable resistance profile characterized by activity against most NRTI-resistant viruses and a low propensity for resistance development (30,34).…”
Section: Discussionmentioning
confidence: 99%
“…These results can be partially explained by base-pairing modes and the structures in the active site of each polymerase. For pols and , which require Watson-Crick base pairing for efficient catalysis (50,51), dCTP is more efficiently incorporated opposite N 2 -G adducts than O 6 -G adducts, because optimal Watson-Crick hydrogen bonding is possible only with N 2 -G adducts but not with O 6 -G adducts. This view would be consistent with recent reports that the S. solfataricus Y family DNA polymerase Dpo4 forms a wobble base pair between C and O 6 -MeG (or O 6 -BzG), and thus the polymerization is inhibited (52,53 may uniquely utilize an Arg for the optimal hydrogen bonding with an incoming dCTP, as shown with yeast Rev1 (34).…”
mentioning
confidence: 99%